PERFORMA SMASH BOLA VOLI DALAM EVENT LIGA MAHASISWA DITINJAU DARI ANTROPOMETRI DAN PENGALAMAN BERTANDING - Fadhli, Nurrul Riyad (Journal of Sport and Exercise Science, 2021)
This study aims to determine whether anthropometry and competing experience greatly affect smash performance. From the characteristics of volleyball, it is a team game sport consisting of 6 players in 1 team with a field size of 18 x 9 meters. And the net as a game barrier with a height of 2.24cm for girls and 2.43cm for men requires athletes to have a supportive height. This research method uses descriptive analysis by analyzing the video matches of the Men's Team of State University of Malang in the 2019 Student League Event. data on the results of the physical condition test conducted by the men's volleyball team, State University of Malang. Competitive experience data were obtained using a questionnaire conducted with the online method. Results From the data, UM players have quite good abilities, and are mentally deficient. It can be seen in the data above the comparison between regional matches and national matches, in regional matches the average smash is 26% and national matches UM players experience a drastic decline in smashes with only 15% spikes, and the player who smashes the most was AD with a total of 142 smashes, DN with 81 smashes. Anthropometric results have an effect on match results, but mental and experiential aspects are very influential when playing matches.